Implementasi CRM (Customer Relationship Management) Di Perpustakaan Daerah Medan - Eva Soraya; Hasan Sazali (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
Customer Relationship Management (CRM) is a management approach that places customers in a process and implementation of the company's marketing strategy. The focus of CRM is Medan City library customers. What is needed by library customers, how to get used to them, and how a library can maintain good relations with library users, all collected in a CRM that provides satisfaction for users and in the end everything is able to tailor and maintain a users’ library. The approach used in this study is a qualitative approach that is descriptive in nature, the data sources of this research are secondary and primary. The data collection technique used is interview, the data analysis technique is descriptive analysis, namely a method that describes research results by examining data obtained from companies and then compared with various theories that support research problems. Based on the results of the research conducted, the conclusion is that the form of CRM (Customer Relationship Management) implementation in increasing and retaining library customers is in accordance with the theory put forward by Lukas (2001) that there are three dimensions, namely the dimensions of people, processes and technology that have been implemented properly. well then the two fundamental elements of customer loyalty have also been implemented and run well by the Medan Regional Library.